PROFESI HUKUM: NILAI-NILAI DAN TANGGUNG JAWAB DALAM KERANGKA NORMA - Lailatut Thoyyibah; Muhammad Asyari Badawi; Mohammad Shollahudin Al Ayubi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The legal profession has an important role in maintaining social balance based on the principles of law and justice. As part of the legal system, legal professionals are not only required to have expertise in their field, but also must uphold professional moral and ethical values. The main values that legal professionals must have include honesty, authenticity, responsibility, independence morals, and moral courage. These values are the basis for carrying out legal duties fairly and with integrity. In addition, professional responsibilities in the legal field are studied within the framework of norms, which include norms as culture, norms as orders and judgments, and norms as laws and legal regulations. These norms function as guidelines that direct the behavior of legal professionals to remain ethical and responsible towards society. Legal professionals are not only required to have technical expertise, but also must apply moral and ethical values in every aspect of their work. Professional responsibilities in the legal field must be in accordance with applicable norms to ensure fairness, transparency and compliance with the law in practice